Case Study : D’Roi F&B Industries / Nur Syuhadah Hashim - Hashim, Nur Syuhadah (2020)
D’Roi F&B Industries is the manufacturer for instant paste and maker of “Bawang Goreng”. All the recipe for instant paste are created by the owner herself